ESTUDOS ORGANIZACIONAIS E FILOSOFIA: A CONTRIBUIÇÃO DE DELEUZE - Maria Fernanda Rios Cavalcanti (RAE: Revista de Administração de Empresas, 2016)
This paper aims to examine some of the contributions of Deleuzian Philosophy to Organization Studies. To do so, first I will do a general reading of his work, examining three landmarks of his philosophy: his concept of difference and its implications; the conception of the subject engendered by it and, finally; the role and relevance of his partnership with Guattari for the realization of his philosophical project. I conclude that Deleuze’s Philosophy can contribute especially for empirical studies in organizations by providing basic assumptions that could guide these studies. This article aims to contribute not only to a better understanding of the complex thought one of the most important philosophers of the twentieth century in the field of Organization Studies, but also wishes to fill a gap in this field concerning the poignant need for philosophical reflection do be made present in it.